ANALISIS PENGARUH HARGA, MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN KONSUMEN MEMBELI MIE INSTAN INDOMIE DI KECAMATAN RANTAU SELATAN KABUPATEN LABUHANBATU - Syafril Rambe (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2013)
This research is intended to analize the influence of prices, trademarks and product quality tosample in the research were taken from 98 indomie selling modest stall spreading in the district statedabove. The data collecting method in this research buy using questionnaire. While the data in theanalyzing method to answer the hypothesis is by making use of multiplied regressive analysis.The result of this research show that the prices, the trademarks, and the product quality, at thesame time positively and significantly affect the customer`s decision to buy instan noodle indomie inRantau Selatan district, Labuhanbatu regency. Mean while the prices, and the trademarks partiallybring more dominan influence than the product quality to the comsumer`s decision to buy indomie inRantau Selatan disctrict, Labuhanbatu regency.